Pengaruh Hololive Indonesia dalam Memperkenalkan Bahasa Indonesia Kepada Penonton Internasional - Mikneya Reyus Liman (Universitas Palangka Raya, 2023)
In the era of globalization, various kinds of people from various parts of the world can be connected and interconnected in various aspects of life. The emergence of the Virtual Youtuber trend in Indonesia has influenced some people outside Indonesia to recognize and be interested in the Indonesian language. The purpose of this scientific article is to examine the rapidly growing Vtuber (Virtual Youtuber) phenomenon and find out the influence of many international Hololive Indonesia fans on their Indonesian language knowledge. The focus of this research is to discuss the development of the Virtual Youtuber industry, especially the impact of language exchange that occurs due to the establishment of an Indonesian branch by the largest company in the Virtual Youtuber industry, Hololive. This article uses the research methods of literature study and virtual observation. The results of the research show the interest and reasons of the audience and fans of Hololive ID talents to learn Indonesian.